Microstructure and Microhardness of AA6061 Aluminum alloy Formed by Cyclic Expansion-extrusion Process: Numerical Simulation and Experimental Evaluation - Manh Tien Nguyen; Truong An Nguyen (Archives of Metallurgy and Materials, 2025)
This paper reports numerical simulation and experimental evaluation of the cyclic expansion-extrusion (CEE) process of AA6061 aluminum alloy. Commercial software Deform 2D was used to simulate the deformation process. The material model is set up for the simulation problem by tensile tests. Simulation results are exploited including stress-strain field during the CEE process. They clearly explain the mechanism of severe plastic deformation (SPD) of the CEE method, one of the methods to create ultrafine grains (UFGs) in microstructures for the studied alloy. Tensile and CEE tests were performed at room temperature. The corresponding experimental results also show changes in the microstructure and microhardness of the test specimens. After the cycles of the CEE process, the average microhardness of the deformed specimens increased by approximately 150% compared to the initial microhardness. The UFGs in microstructures were obtained after 4 CEE cycles. The average grain size in the microstructure has been achieved at about 5÷6 μm from the initial value of 100 μm. The results of the paper show the applicability of the CEE method in the fabrication of UFGs materials for subsequent special forming processes.